Lazareto de Jacarecanga e da Lagoa Funda: varíola, poder e assistência na cidade de Fortaleza (1820-1880) - Martins, Hévila de Lima (2013)
We aim in this dissertation to analyze the constitution, the structure, the operation, the purpose and the implications of the social urban environment expressed in Jacarecanga and Lagoa Funda’s lazarettos, in the nineteenth century, in Fortaleza city. Our purpose consists of developing a study focused on the lazarettos as a place of isolation for individuals affected by smallpox. In this sense we also discuss the practice and the interventions done to stop the smallpox dissemination within the urban environment. We aim to understand how relationship, discourse and practice were established in relation to the people infected by smallpox and to their isolation within the lazarettos as a preventive measure. Understanding the experience with smallpox in the city, represented by the existence of lazareto, implies in investigate the issues associated to urban life in Fortaleza, to its residents, to healing practices and to the everyday life.